NOTARY RESPONSIBILITY FOR GRANTING INCORRECT DATE ON AUTHENTIC DEED - Ni Putu Ayu Bunga Sasmita; I Wayan Novy Purwanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
An authentic deed that made by Notary may lose its perfection if the deed has defects in its form. This article examines cases by a notary that has granted an incorrect date on an authentic deed, as stated in the Court Decision Number 756/Pdt.G/2021/ PN Dps. The aim of this study is to identify the legal consequences of granting an incorrect date to an authentic deed and also the form of notary legal responsibility for granting an incorrect date on the deed that notary made. This article used normative legal research and the approach method used is a statute approach, conceptual approach, and case approach. The results showed that the act by Notary who granted an incorrect date on the authentic deed even though it had received approval from the parties was an "unlawful act" and the authentic deeds becomes degraded by barely having the evidence as a deed under the hand. Legal responsibility of a Notary can be viewed from civil, criminal and administrative aspects.